2003
DOI: 10.1002/hup.502
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term efficacy and therapeutic drug monitoring of sertraline in major depression

Abstract: Maintenance treatment for depression should be considered as a chronic disease management programme. Several studies have reported that sertraline (SRT) can be useful in preventing relapses and recurrent episodes of major depression.Twenty-three outpatients, 14 males and 9 females, affected by major depressive disorder, recurrent (DSM-IV criteria) were included. The patients were prescribed 25-150 mg of SRT for 12 months and were evaluated at baseline (T(0)), after 15 days (T(0.5)), 30 days (T(1)), 6 months (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
1
8
0
1
Order By: Relevance
“…Although the biological activity in desmethylsertraline does not seem to be associated with the clinical efficacy of sertraline, plasma desmethylsertraline level also did not differ between the responders (39.8 AE 7.1 ng/ml) and the nonresponders (44.8 AE 17.1 ng/ml). Some studies have found that therapeutic drug monitoring may be useful for dose optimization as serum concentrations of 25-50 ng/ml appear to be adequate for efficacy (Lundmark and Reis, 2000;Mauri et al, 2003). In contrast, Hong Ng et al (2006) have indicated no visible relationship between plasma sertraline levels and its clinical efficacy.…”
Section: Discussionmentioning
confidence: 88%
“…Although the biological activity in desmethylsertraline does not seem to be associated with the clinical efficacy of sertraline, plasma desmethylsertraline level also did not differ between the responders (39.8 AE 7.1 ng/ml) and the nonresponders (44.8 AE 17.1 ng/ml). Some studies have found that therapeutic drug monitoring may be useful for dose optimization as serum concentrations of 25-50 ng/ml appear to be adequate for efficacy (Lundmark and Reis, 2000;Mauri et al, 2003). In contrast, Hong Ng et al (2006) have indicated no visible relationship between plasma sertraline levels and its clinical efficacy.…”
Section: Discussionmentioning
confidence: 88%
“…Nonetheless, some studies have demonstrated that therapeutic drug monitoring may be useful for dose optimization, because a serum concentration of 25Á50 ng/ml appears to be adequate for efficacy (Lundmark et al 2000;Mauri et al 2003). Since grapefruit juice appears to increase blood sertraline levels, it is possible that grapefruit juice influences the efficacy and/or adverse effects of sertraline.…”
Section: Discussionmentioning
confidence: 97%
“…The oral dosage should be adjusted in patients with hepatic impairment at a dose regimen of 50-100 mg/day. Plasma level determination can be an useful tool to adjust the oral dosage [61,62].…”
Section: Sertralinementioning
confidence: 99%